Evaluation of multidimensional pediatric-psychosomatic inpatient therapy: a pilot study comparing two treatment modalities - Botschek, Tim; Monninger, Maximilian; Schäfer, Dennis; Cevik, Rabia; Memis, Kübra; Müller, Ulrike; Monninger, Martina; Brosig, Burkhard (Frontiers in Psychology, 2023)
Introduction Multidimensional pediatric-psychosomatic inpatient treatment should be considered a highly relevant concept in the German healthcare system. This treatment concept has been successfully integrated to support youth with mental disorders and patients with chronic somatic conditions. Studies on treatment impact and empirical evidence of pediatric-psychosomatic inpatient therapies are rare, despite their clinical significance. Therefore, the study aims to provide initial indications of what constitutes to enhanced treatment effectiveness by comparing two different pediatric-psychosomatic inpatient treatment concepts. The clinics are comparable regarding the treated disorders, which include: dissociative, mood, and somatoform disorders, and psychological factors associated with chronic somatic conditions. Multidimensional treatment in both clinics include components of individual and family therapy, along with group-, art-, music-, creative-, and physio-therapy. Both clinics differed regarding their treatment philosophy in which; Clinic A practiced psychodynamic behavioral elements more strongly, while Clinic B rooted itself more strongly with psychoanalysis and family-dynamic practices. Method Each clinic recruited 25 patients for the study. They completed two questionnaires both at admission and discharge, which measured general behavioral and emotional problems (YSR); and, respectively, difficulties in emotion perception and processing (TAS-26). The effectiveness of the treatment was examined by conducting one-sample t-test and effect sizes for each clinic. To obtain information on differentiating treatment effects, mixed ANOVAs were calculated. For estimating its influence, the treatment duration was taken into account as a covariate calculating an ANCOVA. Results In both settings, treatment effects can be observed regarding internalizing problems. For alexithymia, no effects were seen in Clinic B, while in Clinic A, there was a significant reduction. When comparing both clinics, the ANOVAs showed significant interaction effects displaying advantages for Clinic A in the reduction of internalizing, total behavioral problems and alexithymia. Taking into account the treatment duration as a covariate, those effects level out. Significant differences between the clinics were no longer statistically detectable. Discussion The present study provides substantial preliminary indications on the effectiveness of multidimensional pediatric-psychosomatic inpatient therapy, which seems suitable for alleviating the general symptom burden and problems by identifying and processing emotions. Furthermore, the results indicate that an extended treatment duration may contribute to more pronounced effects.